Electrochemical synthesis and photoelectrochemical properties of a novel RGO/AgNDs composite. Issue 42 (8th April 2015) - Zhang, Xiaomei; Wang, Aming; Ke, Rui; Zhang, Shengyi; Niu, Helin; Mao, Changjie; Song, Jiming; Jin, Baokang; Tian, Yupeng
Abstract : A novel RGO/AgNDs composite was prepared by a one-step electrodeposition method. The RGO/AgNDs composite exhibited excellent photoelectrical conversion and sensitive electrochemical response to H2 O2 . Abstract : A novel composite of Ag nanodendrites (AgNDs) wrapped with reduced graphene oxide (RGO) was prepared via a one-step electrodeposition approach. The characterization results show that three dimensional (3D) AgNDs with cubic phase are enwrapped by RGO sheets in the as-prepared RGO/AgNDs composite. Due to the synergistic effect of AgNDs and RGO, the RGO/AgNDs composite exhibited excellent photoelectrical conversion. Furthermore, due to its good electrochemical response to H2 O2, an electrode modified with the RGO/AgNDs composite was used as a sensor for H2 O2 detection, and the results show that the linear detection range is from 0.08 mM to 2.65 mM.